Evaluation of overall equipment effectiveness in the bottling line packaging process: A case study of the beverage company - Tampubolon, Jusra (OPSI, 2025)
The effectiveness of equipment on the bottling packaging line greatly determines throughput and quality in the high-capacity beverage company. Overall Equipment Effectiveness (OEE) is commonly used to assess performance and map sources of loss. This study evaluates beverage company bottling line using OEE and six big losses based on weekly data from weeks 14–26, including production output (good, reject, total), available time, planned downtime, and unplanned downtime. OEE components were calculated (Availability–Performance–Quality) and decomposed into breakdown, setup & adjustment, idling & minor stoppages, reduced speed, and defect. The results showed an average OEE of 69.35% (68.03–70.79%) with availability at 97.9%, performance at 70.9%, and quality at 99.9%. The dominant loss was reduced speed (≈28.48% of loading time), while setup & adjustment was 0.95%, breakdown 0.89%, idling & minor 0.24%, and defect 0.0895%, which were relatively small. The findings confirm performance as the main constraint; improvements are directed at stabilizing the Filler speed (pacemaker), line balancing & buffering, controlling micro-stops, and predictive maintenance of critical points. Improving performance is projected to be the most effective way to bring OEE closer to the 85% benchmark without compromising quality.